MENUNGGU NASIB RUU PENYANDANG DISABILITAS DI DPR - Agus Rianto (Journal of Law, Society, and Islamic Civilization, 2015)
The Persons with Disabilities in this country are so excited to welcome the bill on Disability which is intended to replace Law No. 4 of 1997 on Persons with Disabilities that are not in accordance with the demands of time, but they were disappointed because the government as if forgetting the Bill, so far about the Disability Bill has not passed into law official. Because of this the Federation of Indonesian Welfare of Persons with Disability (FKPCTI) held an activity entitled "Moving For Disabilities," on August 13, 2015 at the Office of the Human Rights Commission with a demand that Jakarta About Disability Bill be passed into law official.Viewing the contents of the Bill on Disability in fact many things are arranged as an improvement of the provisions ago, such a paradigm shift from a charity-based to a rights-based; change the term "Persons with Disabilities" to "Disability"; alteration of the minimum setting state responsibility be maximizing setting state responsibility for Disability; arrangements regarding accessibility and equal rights and opportunities for Persons with Disabilities; arrangements regarding the fulfillment and protection of various rights of Persons with Disabilities in many areas of life without exception; community participation; the rules governing criminal sanctions; and various restrictions that can not be done against Persons disablitas.